2022
DOI: 10.3389/fpubh.2022.914121
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, attitude, acceptance, and practice of COVID-19 vaccination and associated factors complemented with constructs of health belief model among the general public in South Gondar, Ethiopia: A community-based study

Abstract: IntroductionUnderstanding the epidemiological dynamics of disease control, as well as the effectiveness, compliance, and success of the vaccination program requires an understanding of the local population's knowledge, attitude, and practice regarding the Corona Virus Disease of 2019 (COVID-19) vaccine. Thus, the objective of this study was to assess knowledge, attitude, and practice toward COVID-19 vaccination and associated factors among the general public.MethodsA cross-sectional study was conducted in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Knowledge facilitates the formation of positive attitudes which finally promote the behaviour. The KAP model has been widely used in changing nurses' working behaviour and promoting continuing education (Yisak et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge facilitates the formation of positive attitudes which finally promote the behaviour. The KAP model has been widely used in changing nurses' working behaviour and promoting continuing education (Yisak et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The KAP model has been widely used in changing nurses' working behaviour and promoting continuing education (Yisak et al, 2022).…”
Section: Measurementmentioning
confidence: 99%
“…2 Knowledge, attitude, and practices (KAP) studies of COVID-19 in sub-Saharan Africa have demonstrated positive associations between knowledge of COVID-19 symptoms, transmission, and prevention, and implementation of public health measures such as hand hygiene, social distancing, and facemask use. 3,4 Knowledge of COVID-19 symptoms, transmission, and prevention has also been positively associated with vaccination coverage, [5][6][7] which is one of the most effective strategies for protecting individuals against COVID-19 hospitalization and death. 8,9 COVID-19 vaccines were introduced in Ethiopia in March 2021, initially prioritizing healthcare workers, older adults, and individuals with chronic diseases.…”
Section: Introductionmentioning
confidence: 99%